REPUTASI AUDITOR, KARAKTERISTIK DEWAN KOMISARIS, DAN KEINFORMATIFAN LABA - Sansaloni Butar-Butar Butar-Butar (Jurnal Akuntansi Bisnis, 2014)
The objective of the study is to examine the effect of auditor's reputation and Board of Commissioners independence in improving earnings informativeness. Previous studies suggest that earnings management activities are reflected in abnormal accruals contained in financial statements. In this study, earnings informativeness is measured by the ability of abnormal accruals to predict next year's net income. As the quality of abnormal accruals increased, the predictive content of abnormal accruals is also increased. Using regression analysis, results of the study can be summarized as follows: first, abnormal accruals of company with independent Board of Commissioners has a strong correlation with the earnings one year ahead compared to companies that do not have an independent Board of Commissioners. Second, abnormal accrual of a company that has auditors affiliated with the Big Four has a strong correlation with the earnings one year ahead than firms that auditors are not affiliated with the Big Four accounting firm. Overall, results of the study suggest Board of Commissioners and external auditors play an important role in improving the quality of reported earnings.